Posted by **Laura** on Wednesday, October 28, 2009 at 3:19pm.

prove:(cscx-cotx)^4 x (cscx+cotx)^4 = 1

## Answer This Question

## Related Questions

- trig - express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is ...
- drwls - My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an ...
- calculus - express in sinx 1 1 ---------- + -------- cscx + cotx cscx - cotx and...
- trig - Prove (cscx+cotx)(cscx-cotx)=1
- Math - prove:(cscx-cotx)^4 x (cscx+cotx)^4 = 1
- Precalculus - Simplify:[(cscx-cotx)(cscx+cotx)]/cscx
- Trig - prove (cscx-secx/cscx+secx)=(cotx-1/cotx+1)
- ap calc bc - hi! ok, i know that deriv(cscx) = -cscxcotx and that deriv(cos) = -...
- Pre-Calculus - Find a numerical value of one trigonometric function of x if tanx...
- Math - Im really struggling with these proving identities problems can somebody ...

More Related Questions